2005
DOI: 10.1111/j.1742-4658.2005.04683.x
|View full text |Cite
|
Sign up to set email alerts
|

Calpain 1–titin interactions concentrate calpain 1 in the Z‐band edges and in the N2‐line region within the skeletal myofibril

Abstract: Calpain 1 (microcalpain) and calpain 2 (millicalpain), the best characterized calpains, are known as intracellular calcium-dependent endoproteases and are expressed in different tissues of vertebrates. These ubiquitous cysteine proteases [1] play important roles in a large set of intracellular events [2][3][4][5], particularly in the selective proteolysis of factors involved in the cell cycle [6], during apoptosis in association with caspases [7], or in the cleavage of membrane-cytoskeleton complexes during ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 72 publications
0
64
0
Order By: Relevance
“…Finally, the Ig motifs located at the Z/I junction bind specifically to the giant myofibrillar protein obscurin (ZIg8-ZIg9) [Young et al, 2001], to the ubiquitously expressed Ca 2+ -dependent protease calpain-1 (ZIg8-IIg5) [Raynaud et al, 2005], to sarcomeric actin (Zig-9-IIg-1) and to tropomyosin Raynaud et al, 2004] (Fig. 1).…”
Section: Structure and Function Of Titinmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the Ig motifs located at the Z/I junction bind specifically to the giant myofibrillar protein obscurin (ZIg8-ZIg9) [Young et al, 2001], to the ubiquitously expressed Ca 2+ -dependent protease calpain-1 (ZIg8-IIg5) [Raynaud et al, 2005], to sarcomeric actin (Zig-9-IIg-1) and to tropomyosin Raynaud et al, 2004] (Fig. 1).…”
Section: Structure and Function Of Titinmentioning
confidence: 99%
“…S100A1 inhibits actin binding to the PEVK segment in a Ca 2+ -dependent manner and has been shown to interact with several sites along TTN's extensible region in situ [Yamasaki et al, 2001]. Tropomyosin, in a complex conformation with actin [Raynaud et al, 2004], nebulin (specifically the proline-rich sequences [ Ma and Wang, 2002]), and calpain-1 [Raynaud et al, 2005], also bind to the PEVK region in addition to their binding sites in the TTN Z-disk or Z/I junction regions (Fig. 1).…”
Section: Structure and Function Of Titinmentioning
confidence: 99%
“…3C), indicating that high concentrations of albumin decrease the transcription of the megalin gene. Furthermore, the possibility that the effect of albumin could be due to lysosomal degradation was ruled out, because 0.5 M afilomycin A1 and 100 M U64, inhibitors of lysosomal degradation (25,26), did not change the albumin-induced decrease in megalin protein expression (data not shown).…”
Section: Pathophysiological Concentrations Of Albumin Chronically Altmentioning
confidence: 99%
“…Inmunolocalization studies have shown that both, CAPN1 and CAPN2, are located intracellularly along the Z disk/I band regions in the form of intracellular stores (9). Raynaud et al (10) found that CAPN1 is concentrated on the N1 and N2 line region of titin and suggested that this might constitute a reservoir for the cell. Many calpain substrates, including titin, nebulin, filamin, troponin-T and desmin, which attaches the sarcolemma to the Z-disc, are co-localized and proteolyzed during meat tenderization (9).…”
Section: Sistema Calpaínamentioning
confidence: 99%